Extrinsic Pathway Inhibitor in Elective Surgery: A Comparison with other Coagulation Inhibitors - Sandset, P M; Høgevold, H E; Lyberg, T; Andersson, T R; Abildgaard, U (Thrombosis and Haemostasis, 1989)
Extrinsic coagulation pathway inhibitor may be an important regulator of haemostasis to prevent thrombosis after tissue damage. The functional activity of this inhibitor was determined using a chromogenic substrate assay, and compared to the activities of anti thrombin, heparin cofactor II and protein C during the perioperative period of elective hip replacement (n = 28), cholecystectomy (n = 11), and vascular surgery (n = 5). Peroperatively, all the inhibitors decreased rather similarly and to the same degree as the decrease in albumin concentration. The decreases during hip surgery were about 2-fold the decreases observed during cholecystectomy. A significant peroperative increase in extrinsic pathway inhibitor activity was observed in vascular surgery, probably due to a bolus injection of heparin. Antithrombin, heparin cofactor II and protein C levels normalized on days 3-5 postoperatively in all three patient groups. Sustained low levels of extrinsic pathway inhibitor were observed on postoperative days 1 to 7 in hip surgery patients. Apparently, extrinsic pathway inhibitor is not an acute phase reactant. In uncomplicated surgery, the decreases of the coagulation inhibitor levels are mainly due to hemodilution.
Keywords: Hip surgery; Coagulation inhibitors; Tissue thromboplastin; Extrinsic pathway inhibitor